2009
DOI: 10.1051/vetres/2009036
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the immunogenicity of theTrypanosoma congolensecysteine protease, congopain, through complexation with α2-macroglobulin

Abstract: The protozoan parasite Trypanosoma congolense is the main causative agent of livestock trypanosomosis. Congopain, the major lysosomal cysteine proteinase of T. congolense, contributes to disease pathogenesis, and antibody-mediated inhibition of this enzyme may contribute to mechanisms of trypanotolerance. The potential of different adjuvants to facilitate the production of antibodies that would inhibit congopain activity was evaluated in the present study. Rabbits were immunised with the recombinant catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(59 reference statements)
0
9
0
1
Order By: Relevance
“…VSG has been expressed by several groups in different host cells including insect cell line 14 , yeast 15 and E. coli 16,17 . Furthermore, several other genes from different species of trypanosomes have also been successfully expressed in Pichia pastoris, for instance, acid -mannosidase and trans-sialidase from T. cruzi 18,19 , rhodesain from T. brucei rhodesiense 20 and congopain from T. congolense 21 . In the present study, the VSG gene of T. evansi has been expressed in P. pastoris and assessed its immunoreactivity.…”
mentioning
confidence: 99%
“…VSG has been expressed by several groups in different host cells including insect cell line 14 , yeast 15 and E. coli 16,17 . Furthermore, several other genes from different species of trypanosomes have also been successfully expressed in Pichia pastoris, for instance, acid -mannosidase and trans-sialidase from T. cruzi 18,19 , rhodesain from T. brucei rhodesiense 20 and congopain from T. congolense 21 . In the present study, the VSG gene of T. evansi has been expressed in P. pastoris and assessed its immunoreactivity.…”
mentioning
confidence: 99%
“…In addition to the aforementioned RBC injuries, the apparent membrane fusion, changes in the oligosaccharide composition of the surface of RBC, and mechanical damage “pinching out” caused by the motility of the trypanosomes in the bloodstream [13, 17, 31] induce ultrastructural, biochemical, and antigenic alterations of the RBC, which increases erythrophagocytosis, as shown in Figure 16.…”
Section: Discussionmentioning
confidence: 99%
“…However, insufficient research has been done to associate the structural and biochemical changes in RBCs as consequences of the interaction between RBC and trypanosomes. For example, existing reports list the following as possible mechanisms responsible for RBC injury: mechanical damage produced by the interaction of trypanosomes with RBC [11], adhesion and membrane fusion mediated filopodia [12], immune complexes adsorbed to erythrocytes [13], and biologically active substances released by live or dead trypanosomes which produce erythrocyte injury [14–17]. …”
Section: Introductionmentioning
confidence: 99%
“…Antigen delivery by α 2 M * elicits 100 to 1000-fold enhanced antibody titers against protein and peptide based vaccines and vaccine candidates, such as hepatitis B surface antigen [3] and the HIV envelope gp120 C4-V3 peptide [4]. Complexes of α 2 M * and trypanosomal proteinases have been shown to activate CD4+ T cells more efficiently than antigen alone [14] and to stimulate the production of antibodies that effectively inhibit activity of the enzyme [15]. Furthermore, our laboratory has recently demonstrated that α 2 M * -encapsulation enhances antigen-specific CTL responses and protection against antigen-presenting tumors [7].…”
Section: Discussionmentioning
confidence: 99%